Long Term Outcome of Juvenile Onset Recurrent Respiratory Papillomatosis in University Kebangsaan Medical Centre - Bee See, Goh; Mohd Shakri, Nadhirah; Loh Chen Nee, Jenny (ENT Updates, 2020)
Objective: To review the long term outcome of juvenile onset recurrent respiratory papillomatosis (JORRP) in University Kebangsaan Medical Centre (UKMMC). Methods: A sixteen-year retrospective study – from January 2002 to June 2019 – of patients who presented with JORRP at our hospital was carried out. Results: Nineteen cases were identified with the youngest age of presentation being eight months old. The mean follow-up time was 4.8 years. All patients had glottic papilloma, ten had multi-site involvement, namely at the subglottic, trachea, oropharynx and one case of distal spread to the lungs. The majority (71.4%) of patients with tracheostomy had extralaryngeal spread and shorter surgical intervals (a mean of 3.2 procedures per year). All our patients were treated surgically. Two patients with aggressive disease received a trial of the adjuvant therapies Gardasil and Cidofovir. However, no improvement was observed. Conclusion: The worst prognosis is seen in youngeronset JORRP. Surgery is the mainstay of treatment and patients with aggressive disease may need adjuvant therapy. Unfortunately, there is a lack of a standard protocol for adjuvant therapies. Tracheostomy increases the risk of extralaryngeal spread and aggressive disease, and thus should be reserved for patients with severe airway compromise.